An Online Oral Practice/Assessment Platform: Speak Everywhere - Fukada, Atsushi (IALLT Journal of Language Learning Technologies, 2013)
Despite its obvious importance, it appears that in many foreign language programs, oral practice is not given as much time and attention as it deserves. Or perhaps it is more accurate to say that foreign language professionals recognize the need for more oral practice, but do not have at their disposal a convenient means to provide it. An online oral practice/assessment platform, Speak Everywhere, has been developed to fill this void. It allows instructors without special computer knowledge to quickly create video-based speaking exercises and quizzes for their students to work on outside the classroom. The instructor can access the oral productions that the students submit to the system, and grade them or give individual feedback on them either in text or audio or both. Using its flexible and easy-to-use authoring sub-system, it is possible to create exercises of various formats (e.g. Q&A, repeat after the model, structure drills, role-play, and oral reading).